Evaluasi Kinerja K3 Pada Proyek Pembangunan Gedung Ibrahim Tower Tahap 1 Rumah Sakit Roemani Muhammadiyah Semarang - Alan Adi Nugroho; Eko Muliawan satrio (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
This study evaluates Occupational Health and Safety (OHS) performance in the Ibrahim Tower Phase 1 Construction Project at Roemani Muhammadiyah Hospital, Semarang, using a field-based empirical quantitative descriptive-evaluative approach. The research integrates hazard identification, frequency rate measurement, and assessment of preventive implementation to determine overall safety performance. From 203 identified potential hazards within the project’s SMK3 documentation, 39 were verified as actual occurrences, representing 19.21 percent of the total identified hazards. Frequency Rate calculations based on 985,600 working hours indicate that all actual hazard variables fall within the low-risk category (FR ≤ 5), demonstrating controlled accident intensity. Questionnaire analysis involving managerial and operational personnel reveals good to very good levels of preventive implementation, supporting the low frequency findings. The integration of documented safety systems, empirical verification, quantitative risk measurement, and organizational commitment suggests that the project’s OHS management system functions effectively.